2011
DOI: 10.12938/bifidus.30.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Bifidobacterium bifidum</i> G9-1 on Nasal Symptoms in a Guinea Pig Model of Experimental Allergic Rhinitis

Abstract: Recent studies of several animal models have shown beneficial effects of probiotics against allergic responses. However, few reports have examined the effects of probiotics on allergic nasal symptoms such as sneezing and nasal obstruction in animal models of allergic rhinitis. This study evaluated the efficacy of Bifidobacterium bifidum G9-1 (BBG9-1) on antigen-induced nasal symptoms using guinea pig models of allergic rhinitis. Oral administration of BBG9-1 significantly inhibited antigen-induced allergic nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
4
2
Order By: Relevance
“…Thus, we herein experimentally demonstrated that BBG9-1 alleviates the nasal blockage and relieves the development of nasal hyperresponsiveness induced by a natural allergen. We previously reported that BBG9-1 alleviates not only nasal blockage, but also sneezing induced by the antigen OVA in guinea pigs (11). We are currently unclear why the present results differ from previous findings on the influence of BBG9-1 on allergic sneezing.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, we herein experimentally demonstrated that BBG9-1 alleviates the nasal blockage and relieves the development of nasal hyperresponsiveness induced by a natural allergen. We previously reported that BBG9-1 alleviates not only nasal blockage, but also sneezing induced by the antigen OVA in guinea pigs (11). We are currently unclear why the present results differ from previous findings on the influence of BBG9-1 on allergic sneezing.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously reported that BBG9‐1 alleviates not only nasal blockage, but also sneezing induced by the antigen OVA in guinea pigs . We are currently unclear why the present results differ from previous findings on the influence of BBG9‐1 on allergic sneezing.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Bifidobacterium bifidum G9-1 (BBG9-1) was isolated from a healthy person, and its high level of safety is certified by the fact that BBG9-1 has been used as an intestinal drug for several decades. In addition to its anti-flatulent effect, other health promotion effects of BBG9-1, including regulation of allergic reactions[12,13], hypertriglyceridemia and hyperglycemia[14], have been investigated.…”
Section: Introductionmentioning
confidence: 99%